Loss of social independence in patients with neurofibromatosis type 2: a follow-up study using a national registry in Japan - Hiroto Okoshi; Takashi Yamauchi; Machi Suka; Hiroyuki Yanagisawa; Masazumi Fujii; Chikako Nishigori (Komiyama Printing Co. Ltd, 2023)
Background: For patients with neurofibromatosis type 2 (NF2), maintaining an independent state of living is important. The present study aimed to examine the loss of social independence (i.e., a status that patients can work and go to school) and its contributing factors in patients with NF2 using data from a national registry in Japan. Methods: This longitudinal study used a registry database containing information on patients with NF2 who had submitted initial claims to receive medical expense subsidies between 2004 and 2010. Patients with "employed," "studying," and "housekeeping" categories were classified as "socially independent." Patients who were socially independent at baseline were followed-up for up to nine years. The primary outcome of the present study was the loss of social independence during the follow-up period, which was defined as the change in status from being socially independent to socially dependent. First, we examined longitudinal associations between demographic variables and neurological symptoms at baseline and the loss of social independence. Second, we examined whether the occurrence of neurological symptoms is associated with a loss of social independence in patients. Results: A total of 156 patients were included in the present study. During the follow-up period, 37 (23.7%) patients experienced a loss of social independence. In the first analysis, the multivariate logistic regression model showed that the loss of social independence was significantly more frequent among patients with spinal dysfunction than among patients without. In the second analysis, logistic regression analyses showed that neurological symptoms, including bilateral hearing loss, facial nerve palsy, cerebellar dysfunction, decreased facial sensation, speech dysfunction (dysphagia/dysarthria and aphasia), double vision, blindness, hemiparesis, and seizures, were significantly associated with loss of social independence. Conclusions: The occurrence of various neurological symptoms of NF2 can hinder social independence in the long term. Medical service providers need to observe patients while considering the risks, and provide appropriate support to address neurological symptoms that can restrict social independence, as this will lead to maintaining social engagement.